2022
DOI: 10.1016/j.bjoms.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on orthognathic patients: What have we learned?

Abstract: Background Due to the COVID-19 pandemic orthognathic surgery was suspended in the UK. The effect this had on patients, to date, is unknown. Aim: A multi-centre, cross-sectional survey was conducted in the UK to investigate the health-related impact for patients on the orthognathic surgery pathway, including those on the waiting list for surgery . Method : A structured questionnaire was designed to explore the impact of the pandemic on the patients whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…27 A study by Wemyss investigated the emotional distress of patients on the waiting list for orthognathic surgery, highlighting the psychological distress of dental patients with interrupted treatment, such as orthodontic appliance users. 28 A study by Johnson found that patients with unmet dental needs resorted to coping mechanisms, including turning to community support or medical services, selfmanagement of dental problems and not dealing with dental problems altogether. 29 All the researchers emphasized the need for dental care even during the COVID-19 pandemic, at the risk of worsening diseases, with serious consequences such as tooth loss, an increase in comorbidities due to the worsening of pre-existing diseases and psychological suffering due to the lack of treatment.…”
Section: Quantitative Research United Kingdommentioning
confidence: 99%
“…27 A study by Wemyss investigated the emotional distress of patients on the waiting list for orthognathic surgery, highlighting the psychological distress of dental patients with interrupted treatment, such as orthodontic appliance users. 28 A study by Johnson found that patients with unmet dental needs resorted to coping mechanisms, including turning to community support or medical services, selfmanagement of dental problems and not dealing with dental problems altogether. 29 All the researchers emphasized the need for dental care even during the COVID-19 pandemic, at the risk of worsening diseases, with serious consequences such as tooth loss, an increase in comorbidities due to the worsening of pre-existing diseases and psychological suffering due to the lack of treatment.…”
Section: Quantitative Research United Kingdommentioning
confidence: 99%